2004
DOI: 10.1029/2003jd003598
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation burning in the year 2000: Global burned area estimates from SPOT VEGETATION data

Abstract: [1] The scientific community interested in atmospheric chemistry, gas emissions from vegetation fires, and carbon cycling is currently demanding information on the extent and timing of biomass burning at the global scale. In fact, the area and type of vegetation that is burned on a monthly or annual basis are two of the parameters that provide the greatest uncertainty in the calculation of gas and aerosol emissions and burned biomass. To address this need, an inventory of burned areas at monthly time periods f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
168
0
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 204 publications
(182 citation statements)
references
References 63 publications
(66 reference statements)
6
168
0
8
Order By: Relevance
“…These maps are very useful to visualize the correspondence between the data sets. Summaries of the product's accuracy arranged by continent are also provided [Tansey et al, 2004] products are shown. on the web page given above.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These maps are very useful to visualize the correspondence between the data sets. Summaries of the product's accuracy arranged by continent are also provided [Tansey et al, 2004] products are shown. on the web page given above.…”
Section: Resultsmentioning
confidence: 99%
“…The revisit period of the VEGETATION instrument is around five days. The burnt area algorithm was developed by D. Ershov and colleagues under contract to the Joint Research Centre of the European Commission in the GBA2000 project [Tansey et al, 2004]. The algorithm was used successfully over a wide geographical area, on a number of different vegetation types, in the GBA2000 product and it was felt that it could be adapted for application at the global scale.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has a swath of 2000 km allowing almost daily global coverage. The GBA was derived using a set of regionally specific algorithms, designed to maximise detections [Tansey et al, 2004]. The GBA thematic product consists of monthly non-accumulative binary (burnt -not burnt) maps for the whole of the globe for the year 2000.…”
Section: Datasetsmentioning
confidence: 99%
“…Nowadays it is widely recognised that a significant fraction of the total amount of atmospheric emission is given by the phenomenon of biomass burning; as a result, numerous studies have been dedicated to the estimation of such a contribution by means of the monitoring of active fires and burned areas from remotely sensed data [Generoso et al, 2003;van der Werf et al, 2004;Ito and Penner, 2004]. However, two major limitations remain when estimating global emissions from biomass burning.…”
Section: Introductionmentioning
confidence: 99%